Coherent South American Monsoon Variability During the Last Millennium Revealed Through High‐Resolution Proxy Records. Issue 14 (17th July 2019) - Campos, J. L. P. S.; Cruz, F. W.; Ambrizzi, T.; Deininger, M.; Vuille, M.; Novello, V. F.; Strikis, N. M.
Abstract: The number of paleoprecipitation records from the South American Monsoon domain that cover the last millennium has increased substantially in past years. However, hitherto most studies focused only on regional aspects, thereby neglecting the role of large‐scale monsoon variability and the mechanisms that link proxy locations in space and time. Here we decompose the South American Monsoon into its main modes of variability by applying a Monte Carlo principal component analysis to a compilation of 11 well‐dated summer paleoprecipitation records from tropical South America. The first mode represents changes in precipitation over the core monsoon domain, while the second mode is characterized by high loadings along the fringes of the South American Monsoon over Southeastern South America and the northern monsoon limit. Composite analysis reveals an enhanced monsoon with a wider, rather than a southward displaced, South Atlantic Convergence Zone during the early Little Ice Age, in contrast to previous interpretations. Plain Language Summary: The South American Monsoon is responsible for more than 70% of the annual precipitation falling over tropical South America. Due to the lack of data prior to the middle of the twentieth century, the long‐term variability of the monsoon is poorly understood. Yet there are concerns that increasing greenhouse gas concentrations may significantly modify monsoon behavior in the 21st century. To better understand how the monsoon responds to such perturbations, detailed knowledge of how it varied in the past is crucial. This will facilitate improvements to Earth System Models that are used to project future rainfall changes in the region. Here 11 paleoprecipitation records that span the last millennium are analyzed using statistical techniques that allow extracting the shared variability from all records. Our result highlight how the monsoon responded in space and time to large‐scale perturbations of the climate system, associated with the Little Ice Age and the Medieval Climate Anomaly. Key Points: We use high‐resolution δ 18 O records to decompose the South American Monsoon into its main modes of variability during the last millennium The first mode shows an enhanced monsoon during the Little Ice Age and a weakening during the Medieval Climate Anomaly The second mode represents monsoon variability along the fringes of the monsoon area and indicates periods of widening/contractions of the monsoon axis